External Factors Affecting Lowland Rice Farmers’ Use of Chemical Pesticides in Welala Village, Kolaka Timur Regency, Indonesia - Muhammad Aswar Limi; Hartina Batoa; Awaluddin Hamzah; Edi Dwi Cahyono; Putu Arimbawa; Wa Ode Yusria; Abdul Gafaruddin (Journal of Agricultural Extension, 2019)
The continuous use of chemicals in crops has an impact on food safety of chemicals residues produced for consumption. Understanding about the impact of using chemicals that are not wise for plants by actors or producers of food is needed. The purpose of this study was to determine the role of farmer institutions and government policies on farmer's behavior in the use of chemical pesticides. Research method by survey method through a questionnaire as data collection instrument. The research location in Welala Village, Kolaka Timur (Koltim) Regency that has been cultivating lowland rice since the 1980s. The population of this study was 273 lowland rice farmers. The sampling technique by simple random sampling is as much as 20% of the total population so that the number of samples is 55 respondents. Descriptive data analysis, spearman rank correlation analysis and multiple regression with SPSS program. The results showed that farmer's behavior in the use of chemical pesticides was not as recommended. External factors that influence the behavior of farmers in the use of pesticides are the role of farmer institutions in making group rules and so the existence of government policies as the use of chemical pesticides guidelines.